MERAJUT TOLERANSI ANTAR UMAT BERAGAMA : Studi Tentang Penanaman Sikap dan Nilai-nilai Toleransi Antar Umat Beragama di Kabupaten Jombang - Noor Fatikah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Tolerance is not merely an expression, but must be manifested in everyday life. Interfaith relations have long been synchronized and tolerant. Even with strong mutual cooperation in society, it is possible to build tolerance. In light of the COVID-19 pandemic, there is a need to develop attitudes and values of tolerance. During this pandemic, it is an opportune time to strengthen collective attitudes and actions, fostering tolerance, mutual assistance among communities, and mutual trust, regardless of religion, ethnicity, or culture. When members of the community are exposed to the virus, it is hoped that the community will actively participate in showing tolerance. The collective responsibility is to re-establish the attitudes and values of tolerance in Islam correctly to anticipate such situations, beginning with the perception that all beings are equal. Every community has the same rights, and this must be the basis for the attitude of tolerance that has been formed. The research problem is how to weave and instill an attitude of tolerance among religious communities, as well as how to instill values of tolerance during the pandemic in Jombang Regency. This research is field research. The approach used is a qualitative approach. Data collection techniques include interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Data validity testing techniques include extended observation, persistent observation, and triangulation. The research findings contribute to all aspects of community life to prevent the root causes of problems designed to foster division in the form of other forms of hostility. It can build and foster attitudes and values of tolerance among people of different religions without regard to race or ethnicity.